Power Flow in a Large-Core Multimode Fiber under External Perturbation and its Applications - Sen Qian; Yang Xu; Lisheng Zhong; Lei Su (Scientific Reports, 2017)
Abstract Large core optical multimode fiber provides benefits such as a large light-coupling tolerance, easy handling, and delivery of higher light power without undesirable nonlinear effects. In this research, we exploit the effects of external perturbation on the power flow within the large core fiber and present two relevant applications, namely a perturbation sensor and a doughnut beam tuner. Since conventional multimode fiber power flow model does not take into consideration the perturbation effect, we modify the power flow model so that the influence of time varying perturbation can be theoretically analyzed. Based on our theory, we further conduct the numerical simulation and experiments on these two applications. For the fiber vibration sensor, the proposed numerical model shows that the sensor sensitivity depends on the intensity profile of the launched beam and also the higher-order harmonics that were not reported previously can become interferences to affect the signal. For the beam tuner application, we prove both theoretically and experimentally that the doughnut intensity profile at the fiber output can be tuned in real-time by applying external perturbations to the fiber. We expect that the results can be useful to further exploit the external perturbation on large core fiber in various applications.